FAKTOR-FAKTOR TERJADINYA DEMAM BERDARAH DENGUE (DBD) DI KOTA TERNATE (LITERATURE REVIEW) - Lutiah, Siti Jubaida; Azizah, R; Yudhastuti, Ririh; Sulistyorini, Lilis (Dian Nuswantoro Semarang, 2024)
WHO defines Dengue Hemorrhagic Fever (DHF) as a disease caused by the dengue virus, genus Flavivirus, family Flaviviradae. Purpose: of this research is to determine the factors of the occurrence of dengue hemorrhagic fever in the city of Ternate. Methods: The design of this research is a study of population literature. This research is a scientific journal related to public knowledge about the factors that occur in Dengue Hemorrhagic Fever, with dengue hemorrhagic fever as a variable. Results: Results Based on this research showed that research in 6 journals was obtained related to public knowledge about the factors for the occurrence of DHF. There were 6 journals, namely there was a relationship between knowledge in the factors of the occurrence of the disease in terms of knowledge about the occurrence of DHF. Conclusion: From the results of research on 6 journals, it can be related to the community about the factors that occurits pdengue fever. Obtained 4 journals that say there is a relationship between the influence of climate and the epidemiology of DHF events in the factors of the occurrence of DHF with a high percentage value in terms of occurrenceits pdengue fever.